Sistem Pakar Deteksi Dini Gangguan Mata dan Syaraf Akibat Penggunaan Smartphone - Eko - Purwanto; Vihi Atina; Ema Sagita Desylawati (Jurnal Informatika Upgris, 2017)
Smartphone users are increasing from 1.4 billion smartphone users 176 million of them are smartphone addicts. Most smartphone users do not know about any health problems that can be generated from this smart phone. So it takes an expert system to facilitate users as an early detection for the user's personal health.In the manufacture of Expert System Detection Health Problems Due to Use of Smartphone is using Certainty Factor method to calculate the percentage level of certainty of disease. The tools used in system development are: Flowchart, Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD). System development method used is Prototype on the basis of this method can be evaluated by the user until the specifications obtained in accordance with the wishes of users